DIGITALISASI HADITS: PERKEMBANGAN DAN TANTANGAN DI ERA MODERN - Hidayah, Ilhamiyatul; Musaddad, Endad (Yayasan Baitul Hikmah al-Zain, 2025)
This article examines hadith digitalization as both an epistemological shift and a technological transformation that reshapes how Muslims engage with prophetic traditions in the modern age. Through a qualitative literature-based approach, the study traces the evolving forms of digital hadith representation, ranging from e-books and mobile applications to takhrij software and social media platforms. It analyzes how these digital spaces reconfigure the frameworks of transmission, authentication, and interpretation. The findings reveal that digitalization greatly enhances public access to hadith literature, democratizes textual dissemination, and enables faster, more flexible learning across geographic boundaries. However, these benefits are counterbalanced by emerging risks such as the proliferation of fabricated hadiths, the erosion of traditional scholarly authority, and the algorithmic bias that privileges viral content over verified religious knowledge. The study argues that hadith digitalization is not merely a change in medium, but a redefinition of the epistemic landscape—one that demands ethical safeguards, robust digital religious literacy, and strategic collaboration between scholars and technologists to ensure that the transmission of prophetic knowledge remains authentic, contextually relevant, and epistemologically sound in today’s interconnected world.